Sex-specific pace-of-life syndromes. (25th April 2019) - Moschilla, Joe A; Tomkins, Joseph L; Simmons, Leigh W
Abstract: The pace-of-life syndrome (POLS) hypothesis considers an animal's behavior, physiology, and life history as nonindependent components of a single integrated phenotype. However, frequent deviations from the expected correlations between POLS traits suggest that these relationships may be context, and potentially, sex dependent. To determine whether the sexes express distinct POLS trait covariance structures, we observed the behavior (mobility, latency to emerge from a shelter), physiology (mass-specific metabolic rate), and life history (life span, development time) of male and female Australian field crickets ( Teleogryllus oceanicus ). Path analysis modeling suggested that POLS trait covariation differed between the sexes. Although neither sex displayed the complete integration of traits predicted by the POLS hypothesis, females did display greater overall integration with a significant negative correlation between metabolic rate and risk-taking behavior but with life-history traits varying independently. In males, however, there was no clear association between traits. These results suggest that T. oceanicus do indeed display sex-specific trait covariance structures, emphasizing the importance of acknowledging sex in assessments of POLS. Abstract : Behavior is believed to be explained by an animal's physiology and life history. Differences in these traits could account for the variation in behavior seen among individuals from the same population. But could differences in physiology and life history also explain why males and females behave differently? Surprisingly, we find that male and female field crickets actually behave similarly but that physiology and life history affect the behavior of the sexes in different ways.